Reality or utopia: eradication of the AIDS epidemic in Guinea-Bissau by 2030 - Amiry Monteiro Sanca; Daila Alena Raenck da Silva; Cristianne Maria Famer Rocha; Deise Lisboa Riquinho (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to reflect on the implementation of an integrated strategy to eradicate the Acquired Immunodeficiency Syndrome (AIDS) epidemic in Guinea-Bissau by 2030. Methods: a reflective study. Reflection: Guinea-Bissau is a Portuguese-speaking country located in Sub-Saharan Africa, in constant political and economic instability. Among its characteristics are sociocultural diversity and high rates of morbidity and mortality from causes related to infection by the Human Immunodeficiency Virus. In the quest to eradicate the AIDS epidemic by 2030, instituted especially by the United Nations, it is noted that political and socio-cultural factors transformed eradication of the AIDS epidemic by 2030 into a utopia. Final Considerations: international strategies, although ambitious, are considered opportunities for countries to propose and build public policies capable of changing the existing reality.